2023
DOI: 10.1002/adma.202212024
|View full text |Cite
|
Sign up to set email alerts
|

Full Site‐Specific Addressability in DNA Origami‐Templated Silica Nanostructures

Abstract: DNA nanotechnology allows for the fabrication of nanometer‐sized objects with high precision and selective addressability as a result of the programmable hybridization of complementary DNA strands. Such structures can template the formation of other materials, including metals and complex silica nanostructures, where the silica shell simultaneously acts to protect the DNA from external detrimental factors. However, the formation of silica nanostructures with site‐specific addressability has thus far not been e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Compared to room temperature, silicification on 6HB at a higher temperature of 35 °C led to more aggregation after two-day incubation (AFM images in Supporting Information Figure S5). This result is consistent with what was reported in previous work, 36 suggesting higher temperature significantly increases kinetics of silicification on DNA origami and thus elevates aggregation. When silicification was extended to 4 days, we observed a clear height difference between the two samples.…”
Section: ■ Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Compared to room temperature, silicification on 6HB at a higher temperature of 35 °C led to more aggregation after two-day incubation (AFM images in Supporting Information Figure S5). This result is consistent with what was reported in previous work, 36 suggesting higher temperature significantly increases kinetics of silicification on DNA origami and thus elevates aggregation. When silicification was extended to 4 days, we observed a clear height difference between the two samples.…”
Section: ■ Resultssupporting
confidence: 93%
“…While there may have been a small degree of silica growth also on the double-stranded brushes, it was not detectable in the AFM images. In previous work, 36 it was observed that silica preferetially grew at locations where short DNA duplexes were attached. Our AFM images showed the silicification primarily takes place on or very close to the 6HB DNA origmai surface, when using long, double-stranded DNA brushes.…”
Section: ■ Resultsmentioning
confidence: 93%
See 3 more Smart Citations